2016
DOI: 10.1111/odi.12472
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome–systemic diseases connection

Abstract: The human microbiome consists of all microorganisms occupying the skin, mucous membranes and intestinal tract of the human body. The contact of the mucosal immune system with the human microbiome is a balanced interplay between defence mechanisms of the immune system and symbiotic or pathogenic microbial factors, such as microbial antigens and metabolites. In systemic autoimmune diseases (SADs) such as rheumatoid arthritis, systemic lupus erythematosus and Sjögren's syndrome, the immune system is deranged to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 184 publications
(261 reference statements)
2
73
0
1
Order By: Relevance
“…Furthermore, Porphyromonas gingivalis, a bacterium linked to the pathogenesis of the periodontitis, has the unique ability to convert the amino acid arginine to the amino acid citrulline: a process called citrullination, through the production of peptidylarginine deiminase. The protein, which contains the amino acid citrulline, is recognized by the autoantibodies ACPA that are highly specific for RA [49]. Recently, Brusca et al [50] found that there were more organisms than simply P. gingivalis which cause periodontal disease (i.e.…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Furthermore, Porphyromonas gingivalis, a bacterium linked to the pathogenesis of the periodontitis, has the unique ability to convert the amino acid arginine to the amino acid citrulline: a process called citrullination, through the production of peptidylarginine deiminase. The protein, which contains the amino acid citrulline, is recognized by the autoantibodies ACPA that are highly specific for RA [49]. Recently, Brusca et al [50] found that there were more organisms than simply P. gingivalis which cause periodontal disease (i.e.…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…In addition, the presence of pathogens may worsen the symptoms of these diseases. In the oral cavity, saliva is the main factor that maintains microbial homeostasis and this is exemplified in SS where the reduction in saliva disturbs the oral community and leads to dental caries and oral candidiasis (Zarco et al, 2012;Krishnan et al, 2016;van der Meulen et al, 2016).…”
Section: Microbiome and Diseasementioning
confidence: 99%
“…We believe that the realization of the complexity of interactions between the microbiome and the host, that is, this dynamic interface, is of paramount importance for developing precision diagnostics and therapies. Nevertheless, there is still much work to be carried out in order to establish the role of the microbiome in the pathogenesis of autoimmune disease (Krishnan et al, 2016;van der Meulen et al, 2016). We and others think that future research in this area will provide the bases for relevant personalized medicine (Zarco et al, 2012).…”
Section: Oral Diseasesmentioning
confidence: 99%
“…In recent years, several studies have suggested a link between human microbiome and the development of a number of pathological conditions, including autoimmune diseases [1,2]. In particular, the advent of new technologies allowed the characterization of functional properties and composition of microbial communities [3].…”
Section: Introductionmentioning
confidence: 99%